2022
DOI: 10.3389/fpubh.2022.785254
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Working in the Heat Whilst Pregnant: Insights From Gambian Women Farmers in the Face of Climate Change

Abstract: BackgroundThe expected increase in heat in The Gambia is one of the most significant health threats caused by climate change. However, little is known about the gendered dynamics of exposure and response to heat stress, including women's perceived health risks, their adaptation strategies to heat, and their perceptions of climate change. This research project aims to answer the question of whether and how pregnant farmers in The Gambia perceive and act upon occupational heat stress and its health impacts on bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Adaptation options may be limited in this region due to limited economic capacity, specifically the affordability of space cooling. Emerging research in African settings has identified some low costs interventions, including cool roofs, and behaviour change interventions for reducing occupational heat risks (Spencer et al 2022). This study supports the need for increased prevention of heat-related risks in Africa, including the adoption of public health measures such as heat health action plans.…”
Section: Discussionsupporting
confidence: 65%
“…Adaptation options may be limited in this region due to limited economic capacity, specifically the affordability of space cooling. Emerging research in African settings has identified some low costs interventions, including cool roofs, and behaviour change interventions for reducing occupational heat risks (Spencer et al 2022). This study supports the need for increased prevention of heat-related risks in Africa, including the adoption of public health measures such as heat health action plans.…”
Section: Discussionsupporting
confidence: 65%
“…Heat can be perceived as a barrier to engaging in outdoor activities (Caperchoine et al 2009 ) and may deter women from physical activity. Additionally, many women have to work in high temperatures until late in their pregnancy (Spencer et al 2022 ). However, there is a lack of evidence on the pathophysiological mechanisms and outcomes that are needed to inform clinical practice and public health strategies to manage heat risks and reduce impacts on mothers and babies.…”
Section: Introductionmentioning
confidence: 99%
“… 38 For subsistence farmers, the pressures are often different, but the inability to avoid the heat is a shared problem, as detailed in our qualitative analysis of heat perception during pregnancy in this population. 39 …”
Section: Discussionmentioning
confidence: 99%